ANALYSIS OF TEMPERATURE DISTRIBUTION OF HEAT TRANSFER COEFFICIENT IN COOLING SYSTEM (SIMULATION) USING POROUS MEDIA WITH POROSITY VARIATION - Ahmad Hamim Su'udy; Eko Siswanto; Rudy Soenoko (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2017)
Abstract: Internal combustion engine is an engine that is old enough and today has much alternative energy that is found to shift from the role of motor fuel, The cooling system in internal combustion engine, if not handled properly will cause something that is fatal is the occurrence of overheating. Cooling during this time using the fin and radiator, and research continues to grow in terms of heat transfer, that is by using porous media, with the help of computer simulation then the role of the fin and radiator can be replaced with porous media with porosity variation 10%, 15%, 20% 25%, 30% so that the temperature distribution will be obtained. The result of the research by using simulation shows that the porosity value of porous media, the temperature distribution value is also bigger. The lower porosity of the value of (h) the heat transfer coefficient will increase.